Effects of peer assessment within the context of spherical video-based virtual reality on EFL students’ English-Speaking performance and learning perceptions - Chien, Shu-Yun; Hwang, Gwo-Jen; Jong, Morris Siu-Yung (Computers and education, 2020)
English has been recognized as a means of communication around the globe. However, owing to the lack of realistic English practicing contexts, EFL (English as Foreign Language) students generally have few opportunities to communicate with people in English, not to mention to get feedback from others for making reflections. In this study, a spherical video-based virtual reality (SVVR) environment was developed to situate students in authentic English-speaking contexts; moreover, the peer assessment (PA) strategy was employed for guiding students to provide comments on peers' speaking performance and to make reflections on their own performance. To evaluate the effectiveness of the proposed approach, an experiment was conducted in a high school English course. The experiment results reveal more positive effects of the peer-assessment-based SVVR approach compared with the non-peer-assessment-based SVVR approach in terms of the learners' English speaking, learning motivation, and critical thinking skills, as well as reducing their English learning anxiety. Moreover, it was found that the ratings of the students were statistically correlated with those of the teacher. This study further analyzed the types of peer comments by categorizing them into four types: Praise, Criticism, Opinion, and Irrelevant. It was found that Praise feedback was helpful for the students' English-speaking performance, while Criticism feedback might have been unfavorable in this case. Additionally, Irrelevant feedback was not significantly correlated with the students’ performance in the earlier PA stage, but had a significantly negative correlation in the later stage. •A spherical video-based VR system was developed for English-speaking training.•An experiment was conducted using the system with the peer assessment approach.•The approach improved English-speaking performance, motivation and critical thinking.•The approach reduced the students' English learning anxiety.•The students' comments were analyzed to see their relations with learning performance.